Efficacy and safety of lopinavir/ritonavir versus efavirenz-based antiretroviral therapy in HIV-infected pregnant Ugandan women. (14th January 2015) - Cohan, Deborah; Natureeba, Paul; Koss, Catherine A.; Plenty, Albert; Luwedde, Flavia; Mwesigwa, Julia; Ades, Veronica; Charlebois, Edwin D.; Gandhi, Monica; Clark, Tamara D.; Nzarubara, Bridget; Achan, Jane; et al.
<x xml:space="preserve">Abstract</x> Objective: Combination antiretroviral therapy (ART) is now the global standard for HIV-infected pregnant and breastfeeding women at all CD4+ cell counts. We compared the efficacy and safety of an efavirenz versus lopinavir/ritonavir regimen for HIV-infected pregnant women initiating ART in rural Uganda. Design: Randomized clinical trial. Methods: We performed a planned secondary analysis comparing viral load suppression (HIV-1 RNA ⩽400 copies/ml), safety, and HIV transmission to infants in a trial designed to test the hypothesis that lopinavir/ritonavir versus efavirenz-based ART would reduce placental malaria (PROMOTE, ClinicalTrials.gov, NCT00993031). HIV-infected, ART-naive pregnant women at 12–28 weeks gestation and any CD4+ cell count were randomized. ART was provided and participants were counseled to breastfeed for 1 year postpartum. Results: The median age of the 389 study participants was 29 years; median CD4+ cell count was 370 cells/μl. At delivery, virologic suppression was 97.6% in the efavirenz arm and 86.0% in the lopinavir/ritonavir arm (P < 0.001). At 48 weeks postpartum, 91.0% of women on efavirenz and 88.4% on lopinavir/ritonavir had viral suppression (P = 0.49). Grade 1 or 2 gastrointestinal adverse events were higher among women on lopinavir/ritonavir versus efavirenz. Only two infants acquired HIV (both in the lopinavir/ritonavir arm), and HIV-free infant survival was similar between study arms: 92.9% (lopinavir/ritonavir) versus 97.2% (efavirenz) (P = 0.10). Conclusion: Virologic suppression at delivery was higher with an efavirenz versus lopinavir/ritonavir-based regimen. However, women in both arms achieved high levels of virologic suppression through 1 year postpartum and the risk of transmission to infants was low.